An expansion of the phenotype in individuals with SYNCRIP-Related Neurodevelopmental Disorder - Tooba Shafiq; Joanna L. Feng; Lindsay Phillips; Kara Murias; Marcia Ferguson; Kristin Baranano; Alaina Acchione; Patricia Kipkemoi; Collins Kipkoech; Eunice Chepkemoi; Amina Abubakar; Charles Newton; et al. (Rare, 2024)
Disruption of genes within the HNRNP gene family has been observed in neurodevelopmental and neurodegenerative diseases. The HNRNP-Related Neurodevelopmental Disorders (HNRNP-RNDDs), while each unique, have been recently described with similar clinical and molecular features across variation in several genes. However, the phenotypic information on these patients is still lacking. In this case series we aim to describe the phenotypes that are associated with SYNCRIP-Related Neurodevelopmental Disorder (SYNCRIP-RNDD). We describe in depth ten novel individuals and one previously published individual with mostly de novo and predicted damaging variants in SYNCRIP, consistent with a diagnosis of SYNCRIP-RNDD. We also describe previously published patients, many of which are from large cohort studies, as well as individuals from patient databases. Here, we expand the phenotype of SYNCRIP-RNDD beyond a generic neurodevelopmental disorder to a variable syndrome consisting of mild to borderline developmental delay/intellectual disability, speech and language delay, behavioral differences such as autism spectrum disorder, structural brain anomalies, hypotonia, and seizures. Inconsistent dysmorphic features were also observed, with the few recurrent findings including long eyelashes, mildly deep-set eyes, prominent ears, and thin or thick lips. This study increases our understanding of SYNCRIP-RNDD, as well as HNRNP-RNDDs broadly.